Middle Interhemispheric Variant of Holoprosencephaly Associated with Diffuse Polymicrogyria - Takanashi, Jun-ichi; Barkovich, A. James; Clegg, Nancy J; Delgado, Mauricio R (American journal of neuroradiology : AJNR, 2003)
An 11-month-old boy was discovered to have a cleft palate, club foot, hypospadias, and myoclonic seizures. No in utero exposure to teratogens was identified. Brain MR imaging revealed a middle interhemispheric fusion variant of holoprosencephaly, diffuse polymicrogyria, and a hypoplastic brain stem; this was a distinctly unusual association of findings. We hypothesize that an unknown genetic factor causes disturbances of cleavage of the prosencephalon as well as neuronal migration and organization.